Epidermal Growth Factor Attenuates Delayed Ionizing Radiation-Induced Tissue Damage in Bone Marrow Transplanted Mice - Pejchal, Jaroslav; Sinkorova, Zuzana; Tichy, Ales; Pruchova, Sarka; Kmochova, Adela; Durisova, Kamila; Cechakova, Lucie; Lierova, Anna; Ondrej, Martin; Nemcova, Marketa; Kubelkova, Klara; Fatorova, Ilona; et al. (Radiation research, 2016)
We examined the effect of epidermal growth factor (EGF) treatment in mice that received bone marrow transplantation (BMT) after 11 Gy whole-body irradiation. C57Bl/6 mice were divided into three treatment groups: 0 Gy; 11 Gy ((60)Co, single dose, 0.51 Gy/min) with BMT (5 × 10(6) bone marrow cells isolated from green fluorescent protein syngeneic mice, 3-4 h postirradiation); and 11 Gy with BMT and EGF (2 mg/kg applied subcutaneously 1, 3 and 5 days postirradiation). Survival data were collected. Bone marrow, peripheral blood count and cytokines, gastrointestine and liver parameters and migration of green fluorescent protein-positive cells were evaluated at 63 days postirradiation. Epidermal growth factor increased survival of irradiated animals that received BMT from 10.7 to 85.7% at 180 days postirradiation. In the BMT group, we found changes in differential bone marrow and blood count, plasma cytokine levels, gastrointestinal tissues and liver at 63 days postirradiation. These alterations were completely or in some parameters at least partially restored by epidermal growth factor. These findings indicate that epidermal growth factor, administered 1, 3 and 5 days postirradiation in combination with bone marrow transplantation, significantly improves long-term prognosis.
Keywords: velikost orgánu; střeva; Cell Count; slezina; Organ Size; Bone Marrow Transplantation; cytokiny; Mitosis; epidermální růstové faktory; EGF Family of Proteins; radiační poranění; počet buněk; bezpečnost; transplantace kostní dřeně; Spleen; Time Factors; Radiation Injuries; Dose-Response Relationship, Radiation; Animals; ženské pohlaví; zvířata; Bone Marrow; časové faktory; kostní dřeň; myši; apoptóza; vztah dávky záření a odpovědi; Cytokines; mitóza; celotělové ozáření; Intestines; Safety; Mice; Female; Whole-Body Irradiation; Apoptosis